First data about the Papilionoidea from Khara- Adzragyn-Nuruu Protected Area (South-Western Mongolia) (Lepidoptera: Papilionoidea) - R. V. Yakovlev (SHILAP, 2019)
The article gives for the first time the list of the Papilionoidea, collected in July on the territory of Khara-Adzragyn-Nuruu Protected Area (Gobi-Altai aimak, Mongolia). The list includes 26 species, three of them are endemics of the Mongolian Altai: Tongeia bisudu Zhdanko & Jakovlev, 2001, Agrodiaetus mediator Dantchenko & Churkin, 2003 (Lycaenidae), and Erebia chastilovi Churkin, 2003 (Nymphalidae).